Strategi Travel UMKM Mengakses Kontrak Pemerintah: SWOT dan Business Model Canvas (studi kasus: QRS Travel) - Ria Aulia; Elena .; Iwan Tri Setiawan (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the travel service industry have significant opportunities to participate in public procurement through Indonesia’s Electronic Procurement Service (LPSE). However, many travel MSMEs remain insufficiently prepared due to limited digital capabilities, weak organizational governance, inadequate legal and administrative compliance, and the absence of structured business development strategies. This study aims to analyze the internal and external business environment of QRS Travel, formulate strategic development initiatives, and develop a business model to improve organizational readiness for government procurement participation. A qualitative case study approach was employed using data collected through in-depth interviews, observations, document analysis, focus group discussions, and a review of relevant procurement regulations. The data were analyzed using the Strengths, Weaknesses, Opportunities, and Threats (SWOT) framework integrated with the Business Model Canvas (BMC). The findings reveal that digital capability, organizational governance, legal compliance, strategic partnerships, and human resource development are the primary determinants of organizational readiness for entering the government procurement market. The integration of SWOT and BMC produced strategic recommendations emphasizing digital transformation, business model innovation, governance improvement, and partnership expansion. These findings provide practical guidance for travel MSMEs seeking to strengthen their competitiveness and expand access to government procurement opportunities while contributing to the strategic management literature on MSME development in the digital procurement ecosystem.